The influence of internal auditor towards fraud on mining companies: Indonesia stock exchange - Iman Harymawan, Hasna Marwa Almira, Iswajuni, (Opción, 2020)
Financial statement fraud (fraud) is more difficult to detect than the error because the employee or management is trying to hide the fraud. The purpose of this study was to examine the influence of internal auditor experience and internal control disclosure on fraud. The dependent variable in this study was fraud, while the independent variable was the internal auditor experience and internal control disclosure. The result showed that the internal auditor experience variable had no influence on fraud, while the internal control disclosure had an influence on fraud. The result of the study was expected to be useful as input and additional empirical evidence regarding the influence of the internal auditor experience.